2013
DOI: 10.4103/0970-9290.118356
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antimicrobial potential of 10% ginger extract against Streptococcus mutans, Candida albicans, and Enterococcus faecalis: An in vitro study

Abstract: 10% ethanolic ginger extract was found to possess antimicrobial potential against all the three pathogens used in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 9 publications
1
24
0
1
Order By: Relevance
“…About the extract of ginger in the study by Giriraju and Yunus [31] using the agar disc diffusion test, a 10% ethanolic extract exhibited good antimicrobial potential against Streptococcus mutans, E. faecalis, and C. albicans, with inhibition zones of 8, 14, and 11 mm, respectively. However, the authors concluded that further studies are necessary to evaluate the practical and economic feasibility of this extract and to recommend its use in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…About the extract of ginger in the study by Giriraju and Yunus [31] using the agar disc diffusion test, a 10% ethanolic extract exhibited good antimicrobial potential against Streptococcus mutans, E. faecalis, and C. albicans, with inhibition zones of 8, 14, and 11 mm, respectively. However, the authors concluded that further studies are necessary to evaluate the practical and economic feasibility of this extract and to recommend its use in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…[13] A study that examined the antimicrobial properties of ginger extract 10% indicated that minimum inhibitory concentration was 2.5% in the ethanolic extract of ginger and inhibitory properties of this plant on bacteria were confirmed; as a result, this plant can be used as an antifungal compound. [14] In a review article that examined active compounds of ginger for the treatment of various diseases, the results showed that the rhizome of the plant has appropriate antibacterial and antifungal properties. [4] Studies show that substances such as [10]-gingerol and [12]-gingerol can play an important role in antimicrobial properties of ginger rhizome extract.…”
Section: Discussionmentioning
confidence: 99%
“…[ [29][30][31] However, it comes in disagreement with Gull et al (2012) [32] who found that the total ethanolic ginger extract possessed poor antimicrobial eff ect. This might be attributed to the diff erence in susceptibility of the tested extract against diff erent types of microorganisms, since the extract was tested against eight types of clinical bacterial isolates, other than E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…All plants extracts used in the present study have been found to be less eff ective against E. faecalis than (NaOCl 5.25%), this might be attributed to the high concentration of NaOCl in comparison to other studies that used (NaOCl 2%)as a positive control. [24,26,30,42] …”
Section: Discussionmentioning
confidence: 99%